Diagnostic and therapeutic hysteroscopy in Ethiopia: a retrospective study on practice and outcomes - Saron Teka; Mustefa Negash; Samson Zegeye; Endale Yigezu; Melkamu Siferih (BMC Women's Health)
Abstract Background Hysteroscopy is considered the standard for evaluating the uterine cavity. Limited data exists regarding hysteroscopy in Ethiopia. Therefore, the objective of the study was to describe the diagnostic and operative hysteroscopic procedures at St. Paul’s Hospital. Methodology A three-year retrospective descriptive study examined patients who underwent diagnostic and therapeutic hysteroscopy at the Center for Fertility and Reproductive Medicine, St. Paul’s Hospital Millennium Medical College in Addis Ababa, Ethiopia, from June 2018 to June 2021. Descriptive statistics were employed to summarize the findings observed during the hysteroscopy procedures. Result A total of 328 patient records underwent review and analysis in the study. The mean participant age was 31.9 years (31.9 ± 5.1 years), with about 81.4% being nulliparous. Primary infertility (48.5%) was the leading indication for hysteroscopic evaluation, followed by secondary amenorrhea (18%), secondary infertility (17.4%), and abnormal uterine bleeding (8.8%). Concerning hysteroscopic procedures, 6.1% of participants exhibited no uterine cavity abnormalities. Primary hysteroscopy findings comprised intracavitary adhesions (48.2%), endometrial polyps (18%), and submucosal myomas (9%). Adhesiolysis stood out as the foremost surgical procedure, conducted in 48.2% of patients, followed by polypectomy in 20.7%, and fibroid removal in 9%. The complication rate was 2.4%, exclusively during operative hysteroscopy, with uterine perforation observed in six patients. Conclusion Our hysteroscopic evaluation was predominantly requested for primary infertility cases, with secondary amenorrhea, secondary infertility, and abnormal uterine bleeding also being commonly encountered indications. Adhesiolysis was the leading intervention during hysteroscopy, while uterine perforation was the main complication. The hysteroscopy procedures exhibited a strong safety profile, with few complications noted. Future studies should address factors affecting outcomes in diagnostic and operative hysteroscopy, and common factors linked to intrauterine adhesions.